1998
DOI: 10.1021/jm970746g
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Brefeldin A Sulfide Derivatives as Prodrug Candidates with Enhanced Aqueous Solubilities

Abstract: The addition of a variety of thiols to the alpha,beta-unsaturated lactone functionality present in brefeldin A has been carried out, and the resulting sulfides have been oxidized to the corresponding sulfoxides. These sulfoxides have the potential to undergo syn elimination to regenerate brefeldin A. The sulfoxides were more active than the sulfides as cytotoxic agents in a variety of human cancer cell cultures with the activities of the sulfoxides approaching that of brefeldin A itself. The cytotoxicities of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 34 publications
2
24
0
Order By: Relevance
“…Compound 1 was isolated originally from Penicillium decumbens under the name decumbin (Singleton et al, 1958) and later from several microorganisms. It was recognized initially that this compound has a wide range of antibiotic activities and has been studied as a potential anticancer and antiviral prodrug (Takatsuki et al, 1969;Argade et al, 1998a;Argade et al, 1998b;Fox et al, 2001).…”
Section: Identification Of Compounds 1-5mentioning
confidence: 99%
“…Compound 1 was isolated originally from Penicillium decumbens under the name decumbin (Singleton et al, 1958) and later from several microorganisms. It was recognized initially that this compound has a wide range of antibiotic activities and has been studied as a potential anticancer and antiviral prodrug (Takatsuki et al, 1969;Argade et al, 1998a;Argade et al, 1998b;Fox et al, 2001).…”
Section: Identification Of Compounds 1-5mentioning
confidence: 99%
“…This effect of BFA on ARF1 has detrimental consequences on several biological processes, including cell proliferation, cell migration, cell invasion, and cell signaling from the cell surface, both in normal and cancer cells [ 15 , 19 ]. Although the poor bioavailability of BFA precluded its use as anticancer drug [ 20 ], a great deal of effort has been placed into the synthesis of BFA analogues and derivatives [ 21 – 31 ], as well as into the finding and development of new ARF1 and ARF-GEF inhibitors [ 32 – 35 ]. This led, for instance, to the identification of Golgicide A (GCA) [ 36 ] and the development of LG186 [ 33 ], two potent and highly specific inhibitors of GBF1, a cis -Golgi ARF-GEF [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…This view was based in part on a review of the literature, which confirmed that P450 enzymes can transform thioethers by way of sulfoxides into sulfones, and that sulfones can undergo a reverse Michael addition. For example, the synthetic vasodilator thioether flosequinan sulfide is transformed by rat and human liver P450 enzymes into its sulfoxide and sulfone,9 while cancer cell enzymatic oxidation of the synthetic thioether prodrugs of brefeldin yield sulfones, which in turn undergo rapid reverse Michael addition to deliver brefeldin 10. In yet another example of sulfone-mediated reverse Michael addition, the semisynthetic sulfone antibiotic dalfopristin undergoes metabolism in human plasma to give the natural product Michael acceptor pristinamycin IIA 11.…”
mentioning
confidence: 99%